Tinjauan Literatur: Pemakaian Pupuk Kompos Limbah Sayur Kubis (Brasica oleracea var) Terhadap Tanaman Jagung (Zae mays L) - Antahar, Diva; Indrawati, Asmah (Universitas Medan Area, 2025)
Corn (Zea mays L.) is the second strategic food commodity after rice in Indonesia, used as a source of food, animal feed, and industrial raw materials. However, corn production faces the challenge of declining soil fertility due to the excessive use of inorganic fertilizers. A potential alternative is the use of organic fertilizers based on vegetable waste, such as cabbage waste (Brassica oleracea), which is rich in nutrients and beneficial microbes. This study is a literature review that analyzes 20 scientific articles published in 2010–2023 that discuss the nutrient content of cabbage waste, the composting process, and its effectiveness on corn growth. The analysis was carried out narratively and thematically, on data obtained from national and international journals. The results of the study showed that cabbage waste compost, especially those fermented with EM4, contains important elements such as sulfur, calcium, and microbes such as Lactobacillus sp. and Saccharomyces sp., which are able to improve soil structure and increase crop yields. This literature provides a scientific basis for further research and offers sustainable agronomic solutions for farmers through the use of local organic waste.